Circular solar industry supply chain through product technological design changes - Tadas Radavičius; Arvid van der Heide; Wolfram Palitzsch; Tom Rommens; Julius Denafas; Manuela Tvaronavičienė (Insights into Regional Development)
Climate change forces countries and organisations to transition towards renewable energies (RE). The transition requires a substantial amount of renewable energy installations, such as PV (photovoltaic) systems. EU solar cells (main PV panels component) manufacturing capacity in 2019 were only 0,2% compared to the world producers’ capacity. It makes the European Union energy transition dependable on the foreign countries. In addition, the supply chain of the solar industry is facing issues of silicon solar panels having critical raw material (CRM) silver and toxic materials such as lead. The solar panels themselves are a complex combination of components making recovery of the materials a difficult process (Ha, 2020). These and further issues of the lack of circularity in the solar value chain endangers reliable access to solar energy in the long term. The goal of this research is to increase the circularity in the industry by designing technologically the product in a circular way. In order to achieve this goal, the authors blended information provided in the contemporary scientific literature with the shared expertise of producers and other stakeholders. Insights about the possible technological design changes of the solar panels, their issues, and their impact on the supply chain were gathered through an online workshop and EU Horizon 2020 project CIRCUSOL. As a result of the research, the authors proposed product circularity improvement’ steps and specific technological solutions, which would allow enhancing circular solar industry supply chain. The proposed technological solutions are radio-frequency identification (RFID), lead-free ribbons with bismuth as lead replacement, an electrically conductive adhesive (ECA), new industrial cell encapsulation (N.I.C.E), and fluorine-free back sheet.